The Register of Fashion Marketers in Social Media Communication - Nestia, Aulia Mahajjati; Lestari, Yuni Budi; Junaidi, Ahmad (Journal of Authentic Research, 2026)
This study aims to analyse the register used by fashion marketers in social media communication by examining its linguistic characteristics and communicative functions. The study employs a descriptive qualitative approach grounded in the framework of Systemic Functional Linguistics, particularly the concept of register, which comprises field, tenor, and mode. The research data consist of promotional texts in the form of captions and posts taken from fashion marketers’ social media accounts selected through purposive sampling. Data were collected through documentation techniques, while data analysis involved several stages, including data reduction, classification based on the elements of field, tenor, and mode, and interpretation of language functions. The data were analyzed using qualitative thematic analysis to identify patterns of register and communication styles in fashion marketers’ social media content. The analysis began with organizing and reviewing the questionnaire responses and observational data, followed by coding linguistic features such as lexical choices, tone, code-switching, and register elements (field, tenor, and mode). The findings reveal that the register used by fashion marketers is predominantly persuasive and interpersonal, characterized by the use of informal vocabulary, evaluative adjectives, and invitational sentence structures. In terms of field, language is employed to promote fashion products and lifestyles; in terms of tenor, the relationship constructed between marketers and audiences is familiar and egalitarian; meanwhile, in terms of mode, communication is realized in written form with semi-oral characteristics. This study contributes to the field of applied linguistics, particularly to register analysis in the context of digital marketing communications.